Reviewing the relationship between dividend and free cash flow of nonfinancial firms of KSE 100 - Muhammad Muddasir; Saad Ullah Mughal (International Econometric Review (IER), 2022)
Dividend payments are the primary concern of short-term investors, while free cash flow is for long-term investors. In accordance with, the first aim of the study is to the measures of long term and short-term investments and secondly, we have checked whether the dividend payout of the small fifty and big fifty firms are indifferent or not regarding free cash flow. For this research, the sample size we took was all the non-financial listed companies in the KSE 100 Index of Pakistan Stock Exchange (PSX), between the time period starting from 2009 to 2018. We developed four regression models in total to examine our hypothesis and developed our models into two different series. In the end our results came out as expected and we have been able to concur with our defined objectives. We can conclude that, first, there is a strong relationship between long-term and short-term investments and when it comes to payment of dividends, the firms are different depending upon their size. It implies that investors are likely to consider both factors when making investment decisions. This could mean that investors will prioritize companies that demonstrate both strong long-term growth potential and short-term financial stability.
Keywords: G23; G11; F65; O16; 330; Free Cash Flow; Dividend; KSE-100; Non-Financial Firms; Regression Analysis